2021
DOI: 10.1002/isd2.12176
|View full text |Cite
|
Sign up to set email alerts
|

Mobile technology for street trading in Tanzania: A design science research approach for determining user requirements

Abstract: Street trading is an economic activity that is conducted by street traders in numerous urban parts of Tanzania. Street traders use mobile technology to search for markets.This study mapped the wants and needs of Tanzanian street traders and their customers in order to better understand the potential and pitfalls of technology to help their trade activities. Qualitative data were collected using in-depth interviews with 22 street traders and 22 customers. In addition, two focus group discussions with 20 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Moreover, on the contrary, studies (Mlay, 2021; Kulwijila, 2021; Kalimangasi et al , 2021; Nzowa, 2020) on grape farming focused on marketing challenges, postharvest losses, input demand responses and factors affecting marketing performance. In addition, the few studies (Ndauka and Matotola, 2023; Rumanyika et al , 2019) related to production technology and mobile phone technologies for grape smallholder farmers and street traders revealed theoretical and methodological gaps. These studies reported their findings based on the framework of technical efficiency and mobile phone usage while using mixed or qualitative methods to a samples size less than 200 respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, on the contrary, studies (Mlay, 2021; Kulwijila, 2021; Kalimangasi et al , 2021; Nzowa, 2020) on grape farming focused on marketing challenges, postharvest losses, input demand responses and factors affecting marketing performance. In addition, the few studies (Ndauka and Matotola, 2023; Rumanyika et al , 2019) related to production technology and mobile phone technologies for grape smallholder farmers and street traders revealed theoretical and methodological gaps. These studies reported their findings based on the framework of technical efficiency and mobile phone usage while using mixed or qualitative methods to a samples size less than 200 respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Frogdesign, 2012;GSMA & Frogdesign, n.d.;IDEO.org, 2015;University, 2018). The popularization of these approaches fits with the call to develop products that are grounded in the needs and knowledge of end-users in their communities and use context (Rumanyika, Apiola, Mramba, Oyelere, & Tedre, 2021), and design thinking is increasingly promoted as 'good practice' in the international community through aforementioned toolkits, as well as principles like the Principles for Digital Development (Digital Impact Alliance, n.d.) and scientists and practitioners reporting on their experiences with participatory design approaches 11 .…”
Section: From Technocracy To User Centred Thinking and Participatory Approachesmentioning
confidence: 99%